Developing Essay Questions on Prism and Pyramid for the Ability to Understand Mathematical Concept - Ingkha Jameela; Yuriska Destania (Program Studi Tadris Matematika IAIN Salatiga, 2020)
The purpose of this study was making valid and practical essay questions on prism and pyramid for students' ability to understand mathematical concepts. The method used was Research and Development with the Tessmer development model consisting of preliminary stages, self-evaluation, expert review and one-to-one stages. The results of this study were in the form valid and practical (legible) essay questions on prism and pyramid for the ability to understand mathematical concepts. the validity of the questions was seen from the validators' comments on the questions and the practicality (legibility) of the questions is seen from the readability of the questions when given to students. There were 10 valid and practical (legible) questions obtained in the end of this research.